ETHICS OF ONCOLOGICAL CLINICAL TRIALS IN PRIMARY HEALTH CARE IN CUBA - LORENZO, G.; MÉNDEZ, R.; TORRES, O. (MEDECINE LEGALE DROIT MEDICAL, 2025)
Clinical trials are research conducted with humans to evaluate medications or other interventions in the field of medicine. The participation of human beings in research favors the need for close monitoring and compliance with high scientific and ethical standards. At the international level, they are mainly developed in hospitals, but in recent years Primary Health Care has also been incorporated into these investigations. In Cuba, in 2009, began the conduction of oncological clinical trials in the Community Policlinics, institutions belonging to Primary Care. Its objective has been to evaluate the effectiveness and safety of novel biotechnological products such as monoclonal antibodies and therapeutic vaccines for the treatment of cancer. To date, three studies of this type have been carried out, so this work aims to promote an approach to the ethical aspects that have been taken into account for the execution of such clinical trials in this scenario.